2015
DOI: 10.1039/c4sc01317d
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective construction of C-chiral allylic sulfilimines via the iridium-catalyzed allylic amination with S,S-diphenylsulfilimine: asymmetric synthesis of primary allylic amines

Abstract: We have devised a highly regio- and enantioselective iridium-catalyzed allylic amination reaction with the sulfur-stabilized aza-ylide, S,S-diphenylsulfilimine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…[10] In contrast to this,t he study of their nitrogen analogues, sulfilimines, [11] remains comparatively underdeveloped, especially in gold chemistry.C ompared with other nucleophilic nitrenes,s ulfilimines feature inexpensive and easy syntheses, [12] and owing to the strong polarization towards the nitrogen atom, these building blocks can emerge as valuable synthetic intermediates by N À Sb ond cleavage. [13] Nevertheless,tothe best of our knowledge,this versatile and promising metal nitrene precursor has never been successfully applied as ag old carbene precursor although N-sulfonyl sulfilimines were employed by Zhang and co-workers [4b] for the synthesis of a,b-unsaturated amidines (only 2e xamples) in less than 35 %y ield and quite moderate E/Z ratios of 1.5:1 to 2:1. Inspired by previous reports [14] and in line with our interests on gold-catalyzed CÀHannulations (NÀObond cleavage for nitrene transfer), [7b,d,g] we envisioned the generation of a-imino gold carbenes from sulfilimines and ynamides, which could be flexibly and divergently trapped with four types of functional groups attached to either the sulfilimine or ynamide to form four different aza-heterocycles (Scheme 1).…”
mentioning
confidence: 99%
“…[10] In contrast to this,t he study of their nitrogen analogues, sulfilimines, [11] remains comparatively underdeveloped, especially in gold chemistry.C ompared with other nucleophilic nitrenes,s ulfilimines feature inexpensive and easy syntheses, [12] and owing to the strong polarization towards the nitrogen atom, these building blocks can emerge as valuable synthetic intermediates by N À Sb ond cleavage. [13] Nevertheless,tothe best of our knowledge,this versatile and promising metal nitrene precursor has never been successfully applied as ag old carbene precursor although N-sulfonyl sulfilimines were employed by Zhang and co-workers [4b] for the synthesis of a,b-unsaturated amidines (only 2e xamples) in less than 35 %y ield and quite moderate E/Z ratios of 1.5:1 to 2:1. Inspired by previous reports [14] and in line with our interests on gold-catalyzed CÀHannulations (NÀObond cleavage for nitrene transfer), [7b,d,g] we envisioned the generation of a-imino gold carbenes from sulfilimines and ynamides, which could be flexibly and divergently trapped with four types of functional groups attached to either the sulfilimine or ynamide to form four different aza-heterocycles (Scheme 1).…”
mentioning
confidence: 99%
“…Ester 1l was prepared according to the literature . Ester 1g was prepared according to the literature . Ester 1l was prepared by the reaction of ( E )-5-phenyl-2-penten-1-ol with methyl chloroformate.…”
Section: Methodsmentioning
confidence: 99%
“…Evans and co‐workers proposed the Ir‐catalyzed allylic amination of S,S ‐diphenylsulfilimine and also demonstrated that azaylides are valuable class of nucleophiles for both regioslective and enantioselective Ir‐catalyzed allylic amination reaction [68] . Allylic carbonates and benzoates reacted with S,S ‐diphenylsulfilimine and chiral Ir complex derived from [Ir(cod)Cl] 2 and phosphoramidite ligand to form chiral non‐racemic N‐allylic sulfilimines.…”
Section: Classificationmentioning
confidence: 99%